Clinical-genetic findings in a group of subjects with macular dystrophies due to mutations in rare inherited retinopathy genes - Zenteno, Juan C.; Arce-Gonzalez, Rocio; Matsui, Rodrigo; Lopez-Bolaños, Antonio; Montes, Luis; Martinez-Aguilar, Alan; Chacon-Camacho, Oscar F. (Graefe's archive for clinical and experimental ophthalmology, 2023)
Purpose To describe the results of clinical and molecular analyses in a group of patients suffering from inherited macular dystrophies, in which next-generation sequencing (NGS) efficiently detected rare causative mutations. Methods A total of eight unrelated Mexican subjects with a clinical and multimodal imaging diagnosis of macular dystrophy were included. Visual assessment methods included best corrected visual acuity, color fundus photography, Goldmann visual field tests, kinetic perimetry, dark/light adapted chromatic perimetry, full-field electroretinography, autofluorescence imaging, and spectral domain-optical coherence tomography imaging. Genetic screening was performed by means of whole exome sequencing with subsequent Sanger sequencing validation of causal variants. Results All patients exhibited a predominantly macular or cone-dominant disease. Patients’ ages ranged from 12 to 60 years. Three cases had mutations in genes associated with autosomal dominant inheritance ( UNC119 and PRPH2 ) while the remaining five cases had mutations in genes associated with autosomal recessive inheritance ( CNGA3 , POC1B , BEST1 , CYP2U1 , and PROM1 ). Of the total of 11 different pathogenic alleles identified, three were previously unreported disease-causing variants. Conclusions Macular dystrophies can be caused by defects in genes that are not routinely analyzed or not included in NGS gene panels. In this group of patients, whole exome sequencing efficiently detected rare genetic causes of hereditary maculopathies, and our findings contribute to expanding the current knowledge of the clinical and mutational spectrum associated with these disorders.